OPTIMALISASI CARA EKSTRAKSI SARKOTESTA TERHADAP PROSES DAN HASIL VIABILITAS BENIH PEPAYA (Carica papaya L.) - Rita Hartati (Jurnal Optimalisasi, 2017)
result of viability of papaya seed (carica papaya L.) The experimental design used in this study is a complete randomized design (RAL) 4 x 2 factorial pattern with 3 replications consisting of two factors, with There were 8 treatment combinations and 24 experimental units. The materials used in this research are papaya seed, cotton cloth, ash, concentrated H2SO4, and sand. The parameters observed were potential to grow, germination, growth rate and time required 50% from total germination (T50). The results of this study indicate that the average value of viability and vigor is high in the show on the optimization of the way of extraction of cotton cloth (K1). Viability and vigor of sprouts which are better found in local varieties (V1) than with hybrid varieties (V2). Better interaction optimizing the way extraction of sarcotae is found in hybrid varieties (V2) seeds by extraction of cotton cloth (K1). So it can be concluded that the optimization of sarkotesta extraction method is very significant effect on seed viability include growth potential, germination, growth rate and T50% sprout total.Keywords: Sarkotesta extraction, viability, papaya seed (Carica papaya L.).